Agronomic traits at the seedling stage, yield, and fiber quality in two cotton (Gossypium hirsutum L.) cultivars in response to phosphorus deficiency. Issue 2 (3rd March 2020) - Li, Huijie; Wang, Jiawei; Ali, Saif; Iqbal, Babar; Zhang, He; Wang, Shanshan; Chen, Binglin; Zhou, Zhiguo
ABSTRACT: Cotton is critical for phosphorus demands and very sensitive for its deficiency. However, identifying the effect of low-phosphorus tolerance on cotton growth, yield, and fiber quality by reducing phosphorus consumption. This may help to develop phosphorus-tolerant high-yielding cotton cultivars. In a two-year repeated (2015 and 2016) hydroponic experiment (using 0.01 and 1 mM KH2 PO4 ), two cotton cultivars with phosphorus sensitivity (Lu 54; a low-phosphorus sensitive and Yuzaomian 9110; a low-phosphorus tolerant) were screened on the base of agronomic traits and physiological indices through correlation analysis, cluster analysis and principal component analysis from 16 cotton cultivars. Low phosphorus nutrition reduced the plant height, leaf number, leaf area, phosphorus accumulation and biomass in various organs of seedlings. The deficiency negatively affected the morphogenesis of seedlings, as well as yield and fiber quality. Further, these screened cultivars were tested in a pot experiment with 0, 50, 100, 150, 200 kg P2 O5 ha −1 during 2016 and 2017. It was found to have a significant ( P < 0.05) difference in boll number, lint yield, fiber strength, and micronaire at the harvest. Furthermore, after collectively analyzed the characteristics of Lu 54 and Yuzaomian 9110, there were six key indices that could improve the low phosphorus tolerance of cotton cultivars. These were root phosphorus accumulation, stem phosphorus accumulation percentage, leaf and total biomass of seedlings, seed cotton weight per boll and fiber length.